2019
DOI: 10.1093/icvts/ivz144
|View full text |Cite
|
Sign up to set email alerts
|

The role of the angle of the ascending aortic curvature on the development of type A aortic dissection: ascending aortic angulation and dissection

Abstract: OBJECTIVES Type A aortic dissection (TAD), which consists of an intimal tear in the aorta, necessitates emergency surgery. Various risk factors related to aortic dissection have been defined in the literature. According to our hypothesis, a narrower angle of ascending aortic curvature (AAAC) may be an additional risk factor in relation to aortic dissection due to the increased force applied to the aortic wall. METHODS Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…First, our aortic model presents with an in-plane curvature for the ascending portion, while a physiological aorta has typically an out-of-plane curvature. However, previous studies report that ascending aortic curvature can be seen as an independent risk factor for wall dissection or dilation onset [74], where a greater curvature is associated with worsened outcomes [75]. Since here we were focused on the comparison between BAV models, we chose an in-plane curvature aortic model.…”
Section: Limitationsmentioning
confidence: 99%
“…First, our aortic model presents with an in-plane curvature for the ascending portion, while a physiological aorta has typically an out-of-plane curvature. However, previous studies report that ascending aortic curvature can be seen as an independent risk factor for wall dissection or dilation onset [74], where a greater curvature is associated with worsened outcomes [75]. Since here we were focused on the comparison between BAV models, we chose an in-plane curvature aortic model.…”
Section: Limitationsmentioning
confidence: 99%
“…In their study they conducted on 108 patients with Type A aortic dissection, Gode et al [16] found ascending aorta diameter as 52±2.4 mm and they stated that 67% of the patients with dissection were male patients. In their study they conducted on 166 individuals with Type A aortic dissection, Kruger et al [17] found the median value of ascending aorta diameter as 50 mm and they reported that 66% of the patients with dissection were male patients.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of ascending aortic curvature on aortic dilation at follow-up has not been investigated previously. However, one recent cross-sectional study found that a smaller ascending aortic curvature angle may be a risk factor for developing a type-A dissection [20] . Accelerated aortic growth is also a risk factor for aortic dissection and is used in the guidelines to consider lower diameter thresholds for aortic intervention, therefore it may be useful to closely monitor patients with a small ascending aorta curvature radius [3] .…”
Section: Discussionmentioning
confidence: 98%